1997
DOI: 10.1021/bi9704515
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of l-Aspartate Ammonia-Lyase from Escherichia coli,

Abstract: The X-ray crystal structure of l-aspartate ammonia-lyase has been determined to 2.8 A resolution. The enzyme contains three domains, and each domain is composed almost completely of alpha helices. The central domain is composed of five long helices. In the tetramer, these five helices form a 20-helix cluster. Such clusters have also been seen in delta-crystallin and in fumarase. The active site of aspartase has been located in a region that contains side chains from three different subunits. The structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 22 publications
1
83
0
1
Order By: Relevance
“…[4][5][6][7][8][9] However, while the general structure of the ec-ADL protein is similar to those of the previously determined tm-and Pyrobaculum aerophilum (pa-) ADL enzymes, 7,32 significant conformational differences are observed between the proteins. A structural alignment of wild-type ec-ADL with monomers A of tmor pa-ADL yields rms deviations of 2.9 Å and 3.0 Å for all equivalent C α positions, respectively.…”
Section: Overall Fold and Comparison To Previously Determined Adl Strsupporting
confidence: 71%
See 1 more Smart Citation
“…[4][5][6][7][8][9] However, while the general structure of the ec-ADL protein is similar to those of the previously determined tm-and Pyrobaculum aerophilum (pa-) ADL enzymes, 7,32 significant conformational differences are observed between the proteins. A structural alignment of wild-type ec-ADL with monomers A of tmor pa-ADL yields rms deviations of 2.9 Å and 3.0 Å for all equivalent C α positions, respectively.…”
Section: Overall Fold and Comparison To Previously Determined Adl Strsupporting
confidence: 71%
“…The structures of superfamily members has revealed that these enzymes are biologically active as homotetramers, with each monomer comprised of three distinct structural domains. [4][5][6][7][8][9] Although the overall sequence identity between the superfamily members is only ~15-30%, the enzymes are characterized by three regions of highly conserved amino acid residues (denoted C1-C3, respectively). Conserved region C3 contains the signature sequence 294 GSSxxPxKxN 303 (Escherichia coli ADL numbering).…”
Section: Introductionmentioning
confidence: 99%
“…1). The interconversion between these enzyme forms is observed near neutral pH in both the maximum velocity ( V , ) and V,,,/K, pH profiles examined for the reaction in either direction 'The original amino acid numbering scheme has been increased by one since the publication of the high-resolution structure (Shi et al, 1997) to account for the N-terminal methionine that is present in the mature enzyme. (Karsten and Viola, 1991).…”
Section: Ph Studiesmentioning
confidence: 99%
“…YM55-1 [124]. On-going engineering projects will certainly benefit from the recently elucidated X-ray crystal structures of the E. coli aspartase [125] and of the thermostable aspartase from Bacillus sp. YM55-1 [126].…”
Section: Ammonia Lyase Processesmentioning
confidence: 99%